Fundamentals of a Sustainability Profile of Students based on Quantitative Community Building Analyses - María J. Cantalejo; Vilches, Carlos; Navarlaz, Isabel; Maite M. Aldaya; Ferrara, Annapia; Tomasi, Sabrina; Mignani, Chiara; Cavicchi, Alessio; Ghnimi, Sami; Chriki, Sghaier; Dunne, Julie; Catherine Barry-Ryan; et al. (European Journal of Sustainable Development, 2025)
In the context of a growing awareness of environmental challenges and the importance of sustainability values, practices, and choices, this article presents the key findings of the European co-funded NEMOS research project (A New Educational Model of Sustainability Competences through Service-learning) focused on defining the sustainability profile and competencies of students through service-learning in Higher Education. A community-building bottom-up methodology was innovatively applied to identify the competencies needed to define a sustainability profile of students in food-related degrees of five European Higher Education Institutions. The research findings highlight the need for a holistic understanding of students´sustainability, including economic, social, and environmental aspects, as well as the importance of specific sustainability training for lecturers. Furthermore, it underlines the essential role of service-learning as a pedagogical approach to foster students´active participation in the community and to prepare them to address global challenges in a meaningful way. Keywords: higher education, key-competencies, service-learning, sustainability profile